(untitled) (ModaPalavra e-periódico, 2011)
The management and creation of a brand require the development of affection and positive ideas in many contact points between the consumer public and the brand-related expressions, besides attributes found in graphic symbols. The brand management based on innovation of companies that are identified by being innovative through smart strategies of brand’s management and innovation, allows them to situate themselves very positively in the market. The research of trends that focuses on transformation consists in mapping, discovering and knowing the collectivity. That information makes possible to draw plans of action and plans of innovation. In the commercial world of fashion this anticipation is proposed in therms of colors, shapes and textures, besides other perceptive qualities that outline innovation aspects. The continuity of a fashion brand also depends on this percept anticipation shown in products of use and communication.